Preparation method and application of a controllable bone-adhesive and bone-repair promoting hydrogel
By ultrasound regulating the polymerization time and bone repair ability of hydrogels, using natural polymer materials and functional treatments, bone adhesives with good biocompatibility and degradability were prepared, which solved the shortcomings of existing bone adhesives in terms of biocompatibility and regulation and achieved efficient fracture repair.
Patent Information
- Application Number
- CN202310228256.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-10
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-03-10
AI Technical Summary
The existing bone adhesives have complex preparation, low biocompatibility, difficulty in regulating gel time and adhesion strength, and insufficient ability to promote bone repair, resulting in disposable bone adhesive failure in clinical practice.
Ultrasonic regulation of the polymerization time of hydrogels and promoting bone repair, and natural polymer materials such as gelatin and chitosan are used to prepare hydrogels with good biocompatibility and degradability through methacrylic anhydride modification and polyphenol functionalization.
The controllable bone sticking performance and time of hydrogels is achieved, the repair of fractures is accelerated, the adhesion ability and repair effect of bone tissue is improved, and the problem of disposable bone sticking failure in clinical practice is avoided.
Smart Images

Figure CN116531563B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomaterial preparation, and in particular to a preparation method and application of a controllable bone-adhesive and bone-repair promoting hydrogel. Background Art
[0002] Fractures and bone defects are common bone injuries in medicine, and usually require surgical fixation of tissues to achieve tissue repair, such as using metal plates, screws or steel nails to fix bones. Although such methods have a certain therapeutic effect on fractures, they are prone to loosening and infection, leading to the occurrence of other complications. With the advancement of technology, bone adhesives such as polymethyl methacrylate, calcium phosphate and calcium sulfate bone cement have been widely used. As a new alternative, surgical operations have become simpler and faster. However, these products have the defects of poor biocompatibility and no ability to promote bone growth. Therefore, it is necessary to develop bone adhesives with good biocompatibility, adhesion and osteogenic properties. In recent years, although new bone adhesives based on hydrogels have been widely developed, the hydrogel adhesives currently prepared have complex preparation, low biocompatibility, uncontrollable gel time and adhesion strength, and insufficient osteogenic repair ability. It is necessary to develop bone adhesives with excellent biocompatibility and degradability, good bone adhesion properties, and controllable gel time and adhesion strength to solve the problem of one-time bone failure in clinical processes.
[0003] In view of the above problems, the present invention proposes a method for preparing a controllable bone adhesion and bone repair hydrogel and its application. In addition, the hydrogel prepared by the method is mainly composed of natural polymers, has good biocompatibility and degradability, and can meet the needs of implantation. Therefore, a biomedical material for ultrasonically regulating hydrogel polymerization and promoting bone repair is designed to overcome the defects of poor cell compatibility and lack of control of adhesion strength of existing products, so that it has good clinical value. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a controllable bone-adhesive and bone-repair-promoting hydrogel and its application in view of the problems existing in the prior art, and to utilize ultrasonic stimulation to regulate the polymerization time of the hydrogel and promote bone repair, so that the hydrogel material has good biodegradability, biocompatibility and bone adhesion performance; and the bone-adhesive performance and time of the hydrogel can be regulated by ultrasound, so as to accelerate the proliferation and differentiation of osteoblasts and achieve fracture healing.
[0005] Another object of the present invention is to make the hydrogel suitable for use in traumatic bone fractures, bone fracture injuries, bone bonding and promoting bone defect repair.
[0006] The technical measures to achieve the purpose of the present invention are as follows:
[0007] A method for preparing a controllable bone-adhesive and bone-repair promoting hydrogel comprises the following steps:
[0008] Step 1: Dissolve gelatin in a phosphate buffer solution at pH = 7.4, add methacrylic anhydride for modification, dialyze, and freeze-dry to obtain methacrylic anhydride gelatin.
[0009] Step 2: dissolving chitosan in an acidic aqueous solution at pH=5, adding dihydrocaffeic acid and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC), adjusting the solution pH to 5 for reaction, dialyzing, and freeze-drying to obtain dihydrocaffeic acid-modified chitosan.
[0010] Step 3: Calcium nitrate, ammonia water and diammonium hydrogen phosphate solution are mixed and reacted overnight, centrifuged and washed to obtain hydroxyapatite nanoparticles, the hydroxyapatite nanoparticles are dispersed in a Tris-HCl buffer solution, dopamine is added and stirred for 6-12 hours to obtain dopamine-modified hydroxyapatite, the dopamine-modified hydroxyapatite is dispersed in an aqueous solution, methacrylic anhydride is added, and stirred for 3-6 hours to obtain methacrylic anhydride-functionalized hydroxyapatite.
[0011] Step 4: Disperse the carbon material in an aqueous solution, add a polyphenol compound, and add an alkaline solution to adjust the pH value of the mixture to alkaline, the temperature is 25-40°C, and the reaction is stirred for 6-24 hours to obtain a polyphenol-functionalized carbon material.
[0012] Step 5: Disperse the polyphenol-functionalized carbon material obtained in step 4 in an aqueous solution, add ferric chloride hexahydrate, and use the polyphenols on the surface of the carbon material to reduce the ferric chloride hexahydrate to obtain a polyphenol-functionalized carbon-iron material.
[0013] Step 6: Dissolve methacrylic anhydride gelatin in an aqueous solution, add methacrylic anhydride functionalized hydroxyapatite nanoparticles and polyphenol functionalized carbon-iron material to form a mixed solution, then add dihydrocaffeic acid modified chitosan aqueous solution, add initiator sodium persulfate to form a hydrogel prepolymer solution; apply ultrasound under the hydrogel with an ultrasound intensity of 1-3W / cm 2 , the ultrasonic time is 1-10min, and the desired hydrogel can be formed.
[0014] In the above-mentioned method for preparing a controllable bone-adhesive and bone-repair promoting hydrogel, in step 1, 2-6 mL of methacrylic anhydride is added to 5 g of gelatin.
[0015] In the step 2, 0.5-1.5 g of dihydrocaffeic acid is added to 1 g of chitosan, and the mass percentage concentration of EDC is 2-3 wt %.
[0016] In step 3, the mass percentage concentration of dopamine is 0.1-0.5wt%; 15g of dopamine-modified hydroxyapatite is added with 1-4mL of methacrylic anhydride.
[0017] The carbon material in step 4 includes one or more of graphene oxide, single-walled carbon nanotubes, and multi-walled carbon nanotubes.
[0018] The polyphenolic compounds in step 4 include one or more of tannic acid, dihydrocaffeic acid, catechin, gallic acid, gallol, epigallocatechin, epicatechin gallate, and epigallocatechin gallate.
[0019] The specific process of step 4 is as follows:
[0020] S1: dispersing the carbon material in an aqueous solution to form a mass percentage concentration of 0.1-50.0%;
[0021] S2: adding a polyphenol compound having a mass percentage concentration of 0.05-10.0% to step S1;
[0022] S3: adding alkaline solution to step S2 to adjust the solution to alkaline;
[0023] S4: The reaction temperature of step S2 is 20-50°C and the reaction time is 0.1-2h;
[0024] S5: The pH of the solution in step S3 is greater than 7, the reaction temperature is 20-50°C, and the reaction time is 1-24h.
[0025] The mass percentage concentration of methacrylic anhydride gelatin in step 6 of the preparation method of the present invention is 10-15wt%; the chitosan modified by dihydrocaffeic acid is dissolved in an aqueous solution to form a mass percentage concentration of 1-4%, the mass percentage concentration of methacrylic anhydride functionalized hydroxyapatite is 0.5-3%; the mass percentage of polyphenol functionalized carbon material-iron material is 0.01-0.1%; and the concentration of the initiator is 0.05-1%.
[0026] The hydrogel prepared by the method described above is suitable for traumatic bone fractures, bone fracture injuries, bone bonding and promoting bone defect repair.
[0027] A controllable bone adhesion and bone repair promoting hydrogel is prepared according to any of the above methods for preparing the controllable bone adhesion and bone repair promoting hydrogel.
[0028] The hydrogel prepared by the method described above is suitable for the adhesion of bone tissue, and the adhesion performance can be adjusted to achieve bone tissue adhesion and bone repair.
[0029] Compared with the prior art, the present invention has the following beneficial technical effects:
[0030] 1. The present invention uses polyphenol compounds to modify the surface of carbon materials so that they can be better dispersed in hydrogels, and
[0031] The surface polyphenol groups are chelated with iron ions to form a carbon material with sonodynamic effect; not only a conductive network is formed in the hydrogel network, but also the gelation time of the hydrogel can be controlled when ultrasound is applied.
[0032] 2. The present invention uses methacrylic anhydride to modify dopamine-modified hydroxyapatite.
[0033] Anhydride-functionalized hydroxyapatite is used as a crosslinker in the hydrogel system to improve the cohesion of the hydrogel. Hydrogels with different mechanical properties can be obtained by adjusting the concentration of methacrylic anhydride-functionalized hydroxyapatite.
[0034] 3. The present invention uses biodegradable materials as hydrogel substrates. The large amount of polyphenol groups in the materials make the hydrogel
[0035] The hydrogel has good bone tissue adhesion ability; and, by regulating the adhesion time of the hydrogel with ultrasound, the first ultrasound can achieve repeated bone adhesion, preventing the failure of one-time bone adhesion in clinical processes. The second ultrasound can strengthen the adhesion and achieve bone bonding fixation. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1A , Figure 1B , Figure 1C This is a black and white photo of the application of the hydrogel prepared in Example 1 of the present invention.
[0037] Figure 2A , Figure 2B This is a SEM image of the hydrogel prepared in Example 1 of the present invention.
[0038] Figure 3 This is a three-point bending test of the hydrogel prepared in Example 1 of the present invention adhered to New Zealand white rabbit radius bone fragments after one month (curves a, b, and c shown in the graph).
[0039] Figure 4 , a schematic diagram of a comparative test of hydrogels with different adhesion properties obtained by adjusting the concentration of the hydroxyapatite in the present invention.
[0040] Figure 5 , a schematic diagram showing the comparison of the effects of the hydrogel of the present invention on accelerating the gelation time of the hydrogel when ultrasound is applied. DETAILED DESCRIPTION
[0041] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0042] The present invention introduces polyphenol-modified chitosan and polyphenol-functionalized carbon materials to prepare biodegradable adhesive bone glue hydrogel, which has good biocompatibility and a mild gel environment and will not cause secondary damage to the fracture injury site. The bone adhesion performance of the hydrogel is regulated by ultrasound. It has stronger functionality and bone adhesion controllability than existing products, and accelerates the repair of the fracture site.
[0043] The present invention will be further described below in conjunction with specific drawings and implementation examples.
[0044] Figure 1A , Figure 1B , Figure 1C The hydrogel prepared by the present invention is used for the adhesion of New Zealand white rabbit radius bone slices. Ultrasound is used to stimulate gelation. It is observed that the hydrogel can adhere to the bone slices very well, indicating that the hydrogel has excellent bone adhesion performance in vivo.
[0045] FIG2 is a SEM image of the hydrogel prepared by the present invention, Figure 2A The porous structure of the hydrogel was observed and magnified. Figure 2B , the microstructure of the hydrogel was observed, with wrinkles and nanoparticles on the pore walls. It showed that the added methacrylic anhydride functionalized hydroxyapatite nanoparticles and dopamine functionalized graphene oxide-iron materials were distributed in the hydrogel.
[0046] Figure 3 This is a three-point bending test of New Zealand white rabbit radius bone fragments after one month of hydrogel adhesion. Curves a, b, and c in the figure are three-point bending tests of New Zealand white rabbit radius fractures without treatment, radius fractures fixed by traditional fixation, and hydrogel adhesion fracture fragments one month after treatment. It is observed that the hydrogel adhesion can withstand higher loads than other treatment methods. The following is Figure 1:
[0047] Figure 1
[0048] The data in this chart are based on three parallel experiments, three-point bending tests on radial fractures treated in three different ways; this is one of the sets of data that form Figure 3 .
[0049] Figure 4The results show that the present invention obtains hydrogels with different adhesion mechanical properties by experimentally adjusting the concentration of hydroxyapatite functionalized with methacrylic anhydride.
[0050] Figure 5 Experiments have confirmed that surface modification of carbon materials by polyphenol compounds can better disperse them in hydrogels to form and realize chelation of surface polyphenol groups with iron ions, forming carbon materials with sonodynamic effects; the gelation time of hydrogels can be controlled by applying ultrasound of different frequencies and times.
[0051] Embodiment 1:
[0052] A method for preparing a controllable bone-adhesive and bone-repair promoting hydrogel comprises the following steps:
[0053] Step 1: 10 g of gelatin was completely dissolved in 100 mL of phosphate buffer at 60°C, and 8 mL of methacrylic anhydride was added dropwise at a rate of 0.5 mL / min. Then, the mixture was stirred at 50°C for 3 h. 200 mL of phosphate buffer was added to terminate the reaction, and the mixture was placed in a dialysis bag (MW=14000), dialyzed for 7 days, and freeze-dried to obtain methacrylic anhydride gelatin.
[0054] Step 2: Dissolve 0.5 g of chitosan in 100 mL of an acidic aqueous solution at pH = 5, add 1.182 g of dihydrocaffeic acid dissolved in 10 mL of ethanol, and continue to add 2.5 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride dissolved in 40 mL of anhydrous ethanol in a solvent with a volume ratio of 1:1 with water, maintain the pH at 5, and stir the reaction for 12 hours, place it in a dialysis bag (MW = 3500), dialyze it in an aqueous solution at pH 5 for 3 days, and freeze-dry to obtain dihydrocaffeic acid-modified chitosan.
[0055] Step 3: Dissolve 11.9g of calcium nitrate in 100mL of aqueous solution, add diammonium hydrogen phosphate and ammonia solution dropwise, stir and react for 12h, centrifuge and wash with water, and then dry to obtain hydroxyapatite. The obtained hydroxyapatite is dispersed again in 100mL of deionized water, 0.1g of dopamine is added, and after stirring overnight, centrifuge and wash with water to obtain dopamine-modified hydroxyapatite. The dopamine-modified hydroxyapatite is dispersed again in 100mL of aqueous solution, 8mL of methacrylic anhydride is slowly added to react for 3h, centrifuge, and wash with water to obtain methacrylic anhydride-functionalized hydroxyapatite.
[0056] Step 4: Disperse graphene oxide in water to form a concentration of 50 mg / mL, add 0.02 g dopamine and stir for 0.5 h, then add 0.15 g sodium hydroxide and stir for 6 h, centrifuge and wash with water, and dry for use. Disperse the obtained material in 200 mL of aqueous solution, add 0.5 g ferric chloride hexahydrate, then add ammonia water to adjust the pH to an alkaline environment, react at a temperature of 25 ° C for 6 h, centrifuge and wash with water, and dry to obtain dopamine-functionalized graphene oxide-iron material.
[0057] Step 5: Dissolve 1.2g of methacrylic anhydride gelatin obtained in step 1 in 10mL of aqueous solution, add 0.2g of methacrylic anhydride functionalized hydroxyapatite obtained in step 3 and 0.05g of dopamine functionalized graphene oxide-iron material obtained in step 4 to form a mixed solution. Add 0.3g of dihydrocaffeic acid modified chitosan obtained in step 2 and 0.02g of sodium persulfate to the mixed solution to form a hydrogel prepolymer solution; apply ultrasound (1.0MHz, 1W / cm 2 ) for 2 minutes to form the desired hydrogel.
[0058] Embodiment 2:
[0059] Step 1: 10 g of gelatin was completely dissolved in 100 mL of phosphate buffer at 60°C, and 8 mL of methacrylic anhydride was added dropwise at a rate of 0.5 mL / min. Then, the mixture was stirred at 50°C for 3 h. 200 ml of phosphate buffer was added to terminate the reaction, and the mixture was placed in a dialysis bag (MW=14000), dialyzed for 7 days, and freeze-dried to obtain methacrylic anhydride gelatin.
[0060] Step 2: Dissolve 1 g of chitosan in 100 mL of an acidic aqueous solution at pH = 5, add 1.182 g of dihydrocaffeic acid dissolved in 10 mL of ethanol, and continue to add 2.5 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride dissolved in 40 mL of anhydrous ethanol in a solvent with a volume ratio of 1:1 with water, maintain the pH at 5, and stir the reaction for 12 hours, then place in a dialysis bag (MW = 3500), dialyze in an aqueous solution at pH 5 for 3 days, and freeze-dry to obtain dihydrocaffeic acid-modified chitosan.
[0061] Step 3: Dissolve 11.9g of calcium nitrate in 100mL of aqueous solution, add diammonium hydrogen phosphate and ammonia solution dropwise, stir and react for 12h, centrifuge and wash with water, and then dry to obtain hydroxyapatite. The obtained hydroxyapatite is dispersed again in 100mL of deionized water, 0.1g of dopamine is added, and after stirring overnight, centrifuge and wash with water to obtain dopamine-modified hydroxyapatite. The dopamine-modified hydroxyapatite is dispersed again in 100mL of aqueous solution, 8mL of methacrylic anhydride is slowly added to react for 3h, centrifuge, and wash with water to obtain methacrylic anhydride-functionalized hydroxyapatite.
[0062] Step 4: Disperse the single-walled carbon nanotubes in water to form a concentration of 10 mg / mL, add 0.02 g of gallic acid for 1 hour, then add 0.15 g of sodium hydroxide and stir to react for 6 hours, centrifuge and wash with water, and dry for use. Disperse the obtained material in an aqueous solution, add 0.5 g of ferric chloride hexahydrate, then add ammonia water to adjust the pH to an alkaline environment, react at a temperature of 25°C for 12 hours, centrifuge and wash with water, and dry to obtain a gallic acid-functionalized single-walled carbon nanotube-iron material.
[0063] Step 5: Dissolve 1 g of methacrylic anhydride gelatin obtained in step 1 in 10 mL of aqueous solution, add 0.4 g of methacrylic anhydride functionalized hydroxyapatite obtained in step 3 and 0.05 g of gallic acid functionalized single-walled carbon nanotube-iron material obtained in step 5 to form a mixed solution. Add 0.4 g of dihydrocaffeic acid-modified chitosan obtained in step 2 and 0.02 g of sodium persulfate to the mixed solution to form a hydrogel prepolymer solution; apply ultrasound (1.0 MHz, 0.5 W / cm 2 ) stimulation for 5 minutes to form the desired hydrogel.
[0064] Embodiment 3:
[0065] Step 1: 10 g of gelatin was completely dissolved in 100 mL of phosphate buffer at 60°C, and 8 mL of methacrylic anhydride was added dropwise at a rate of 0.5 mL / min. Then, the mixture was stirred at 50°C for 3 h. 200 mL of phosphate buffer was added to terminate the reaction, and the mixture was placed in a dialysis bag (MW=14000), dialyzed for 7 days, and freeze-dried to obtain methacrylic anhydride gelatin.
[0066] Step 2: Dissolve 0.5 g of chitosan in 100 mL of an acidic aqueous solution at pH = 5, add 1.182 g of dihydrocaffeic acid dissolved in 10 mL of ethanol, and continue to add 2.5 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride dissolved in 40 mL of anhydrous ethanol in a solvent with a volume ratio of 1:1 with water, maintain the pH at 5, and stir the reaction for 12 hours, place it in a dialysis bag (MW = 3500), dialyze it in an aqueous solution at pH 5 for 3 days, and freeze-dry to obtain dihydrocaffeic acid-modified chitosan.
[0067] Step 3: Dissolve 11.9g of calcium nitrate in 100mL of aqueous solution, add diammonium hydrogen phosphate and ammonia solution dropwise, stir and react for 12h, centrifuge and wash with water, and then dry to obtain hydroxyapatite. The obtained hydroxyapatite is dispersed again in 100mL of deionized water, 0.1g of dopamine is added, and after stirring overnight, centrifuge and wash with water to obtain dopamine-modified hydroxyapatite. The dopamine-modified hydroxyapatite is dispersed again in 100mL of aqueous solution, 8mL of methacrylic anhydride is slowly added to react for 3h, centrifuge, and wash with water to obtain methacrylic anhydride-functionalized hydroxyapatite.
[0068] Step 4: Disperse graphene oxide in water to form a concentration of 1 mg / mL, add 0.02 g epicatechin gallate and stir for 0.5 h, then add 0.15 g sodium hydroxide and stir for 6 h, centrifuge and wash with water, and dry for use. Disperse the obtained material in 200 mL of aqueous solution, add 0.5 g of ferric chloride hexahydrate, then add ammonia water to adjust the pH to an alkaline environment, react at a temperature of 25 ° C for 6 h, centrifuge and wash with water, and dry to obtain epicatechin gallate functionalized graphene oxide-iron material.
[0069] Step 5: Dissolve 1g of methacrylic anhydride gelatin obtained in step 1 in 10mL of aqueous solution, add 0.2g of methacrylic anhydride functionalized hydroxyapatite obtained in step 3 and 0.05g of epicatechin gallate functionalized graphene oxide-iron material obtained in step 4 to form a mixed solution. Add 0.3g of dihydrocaffeic acid modified chitosan obtained in step 2 and 0.02g of sodium persulfate to the mixed solution to form a hydrogel prepolymer solution; apply ultrasound (1.5MHz, 1W / cm 2 ) for 2 minutes to form the desired hydrogel.
[0070] The present invention introduces polyphenol-modified chitosan and polyphenol-functionalized carbon materials to prepare biodegradable adhesive bone glue hydrogel. Different components are screened and different methods are adopted to form the desired hydrogel. The hydrogel has good biocompatibility and a mild gel environment, which overcomes the defects of existing products. In comparison, the hydrogel has stronger functionality and bone adhesion controllability in application, and accelerates the repair of fractures. The hydrogel is suitable for the repair of various bone tissues such as traumatic fractures, bone cracks, and bone defects.
Claims
1. A method for preparing a controllable bone-adhesive and bone-repairing hydrogel, characterized in that: The following steps are involved: Step 1: dissolving gelatin in a phosphate buffer solution at pH = 7.4, adding methacrylic anhydride for modification, dialyzing, and freeze-drying to obtain methacrylic anhydride gelatin; Step 2: dissolving chitosan in an acidic aqueous solution at pH=5, adding dihydrocaffeic acid and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride EDC, adjusting the solution pH to 5 for reaction, dialyzing, and freeze-drying to obtain dihydrocaffeic acid-modified chitosan; Step 3: Calcium nitrate, ammonia water and diammonium hydrogen phosphate solution are mixed, centrifuged and washed to obtain hydroxyapatite nanoparticles, the hydroxyapatite nanoparticles are dispersed in a Tris-HCl buffer solution, dopamine is added and stirred for 6-12 hours to obtain dopamine-modified hydroxyapatite, the dopamine-modified hydroxyapatite is dispersed in an aqueous solution, methacrylic anhydride is added, and stirred for 3-6 hours to obtain methacrylic anhydride-functionalized hydroxyapatite; Step 4: dispersing the carbon material in an aqueous solution, adding a polyphenol compound, and adding an alkaline solution to adjust the pH value of the mixed solution to alkaline, the temperature is 25-40° C., and stirring for 6-24 hours to react to obtain a polyphenol-functionalized carbon material; Step 5: dispersing the polyphenol-functionalized carbon material obtained in step 4 in an aqueous solution, adding ferric chloride hexahydrate, and reducing the ferric chloride hexahydrate on the surface of the carbon material by using polyphenol in situ to obtain a polyphenol-functionalized carbon-iron nanomaterial; Step 6: Dissolve methacrylic anhydride gelatin in an aqueous solution, add methacrylic anhydride functionalized hydroxyapatite nanoparticles and polyphenol functionalized carbon-iron nanomaterials to form a mixed solution, then add dihydrocaffeic acid modified chitosan aqueous solution, add initiator sodium persulfate to form a hydrogel prepolymer solution; apply ultrasound under the hydrogel prepolymer solution, the ultrasound intensity is 1-3W / cm 2 , the ultrasonic time is 1-10min, and the desired hydrogel can be formed.
2. The method for preparing a controllable bone-adhesive and bone-repairing hydrogel according to claim 1, characterized in that: In the step 1, 2-6 mL of methacrylic anhydride is added to 5 g of gelatin.
3. The method for preparing a controllable bone-adhesive and bone-repairing hydrogel according to claim 1, characterized in that: In the step 2, 0.5-1.5 g of dihydrocaffeic acid is added to 1 g of chitosan, and the mass percentage concentration of EDC is 2-3 wt %.
4. The method for preparing a controllable bone-adhesive and bone-repairing hydrogel according to claim 1, characterized in that: In step 3, the mass percentage concentration of dopamine is 0.1-0.5wt%; 15g of dopamine-modified hydroxyapatite is added with 1-4mL of methacrylic anhydride.
5. The method for preparing a controllable bone-adhesive and bone-repairing hydrogel according to claim 1, characterized in that: The carbon material in step 4 includes one or more of graphene oxide, single-walled carbon nanotubes, and multi-walled carbon nanotubes.
6. The method for preparing a controllable bone-adhesive and bone-repairing hydrogel according to claim 1, characterized in that: The polyphenolic compounds in step 4 include one or more of tannic acid, dihydrocaffeic acid, catechin, gallic acid, gallol, epigallocatechin, epicatechin gallate, and epigallocatechin gallate.
7. The method for preparing a controllable bone-adhesive and bone-repairing hydrogel according to claim 1, characterized in that: The specific process of step 4 is as follows: S1: dispersing the carbon material in an aqueous solution to form a mass percentage concentration of 0.1-50.0%; S2: adding a polyphenol compound having a mass percentage concentration of 0.05-10.0% to step S1; The reaction temperature of step S2 is 20-50°C and the reaction time is 0.1-2h; S3: adding an alkaline solution to step S2 to adjust the solution to alkaline; The solution pH in step S3 is greater than 7, the reaction temperature is 20-50° C., and the reaction time is 1-24 h.
8. The method for preparing a controllable bone-adhesive and bone-repairing hydrogel according to claim 1, characterized in that: The mass percentage concentration of the methacrylic anhydride gelatin in step 6 is 10-15wt%; the chitosan modified by dihydrocaffeic acid is dissolved in the aqueous solution to form a mass percentage concentration of 1-4%, the mass percentage concentration of the methacrylic anhydride functionalized hydroxyapatite is 0.5-3%; the mass percentage concentration of the polyphenol functionalized carbon material-iron nanomaterial is 0.5%; and the mass percentage concentration of the initiator is 0.05-1%.
9. A controllable bone-adhesive and bone-repairing hydrogel, characterized in that: The hydrogel is prepared according to the method for preparing the controllable bone adhesion and bone repair promoting hydrogel according to any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation method for fully degradable magnetic repair hydrogel for bone repair
CN111330089A